Genome-wide association study of familial lung cancer. (19th June 2018) - Byun, Jinyoung; Schwartz, Ann G; Lusk, Christine; Wenzlaff, Angela S; de Andrade, Mariza; Mandal, Diptasri; Gaba, Colette; Yang, Ping; You, Ming; Kupert, Elena Y; Anderson, Marshall W; Han, Younghun; et al.
Abstract : From the GWAS meta-analysis of familial lung cancer risk, novel and imputed rare variants on 4p15.31 and 9p21.3 were identified for squamous cell carcinoma. Several other variants were also confirmed as associated with familial lung cancer including many on chromosome 15q25.1 that reached genome-wide levels of significance ( P < 5 × 10 –8 ). Abstract: To identify genetic variation associated with lung cancer risk, we performed a genome-wide association analysis of 685 lung cancer cases that had a family history of two or more first or second degree relatives compared with 744 controls without lung cancer that were genotyped on an Illumina Human OmniExpressExome-8v1 array. To ensure robust results, we further evaluated these findings using data from six additional studies that were assembled through the Transdisciplinary Research on Cancer of the Lung Consortium comprising 1993 familial cases and 33 690 controls. We performed a meta-analysis after imputation of all variants using the 1000 Genomes Project Phase 1 (version 3 release date September 2013). Analyses were conducted for 9 327 222 SNPs integrating data from the two sources. A novel variant on chromosome 4p15.31 near the LCORL gene and an imputed rare variant intergenic between CDKN2A and IFNA8 on chromosome 9p21.3 were identified at a genome-wide level of significance for squamous cell carcinomas. Additionally, associations of CHRNA3 and CHRNA5 on chromosome 15q25.1 in sporadic lung cancer were confirmed at a genome-wide level of significance in familial lung cancer. Previously identified variants in or near CHRNA2, BRCA2, CYP2A6 for overall lung cancer, TERT, SECISPB2L and RTEL1 for adenocarcinoma and RAD52 and MHC for squamous carcinoma were significantly associated with lung cancer.